Individually Stabilized, Superparamagnetic Nanoparticles with Controlled Shell and Size Leading to Exceptional Stealth Properties and High Relaxivities - Lassenberger, Andrea; Scheberl, Andrea; Stadlbauer, Andreas; Stiglbauer, Alexander; Helbich, Thomas; Reimhult, Erik (ACS Applied Materials and Interfaces, 2017)
Superparamagnetic iron oxide nanoparticles (SPION) have received immense interest for biomedical applications, with the first clinical application as negative contrast agent in magnetic resonance imaging (MRI). However, the first generation MRI contrast agents with dextran-enwrapped, polydisperse iron oxide nanoparticle clusters are limited to imaging of the liver and spleen; this is related to their poor colloidal stability in biological media and inability to evade clearance by the reticuloendothelial system. We investigate the qualitatively different performance of a new generation of individually PEG-grafted core-shell SPION in terms of relaxivity and cell uptake and compare them to benchmark iron oxide contrast agents. These PEG-grafted SPION uniquely enable relaxivity measurements in aqueous suspension without aggregation even at 9.4 T magnetic fields due to their extraordinary colloidal stability. This allows for determination of the size-dependent scaling of relaxivity, which is shown to follow a d2 dependence for identical core-shell structures. The here introduced core-shell SPION with ∼15 nm core diameter yield a higher R2 relaxivity than previous clinically used contrast agents as well as previous generations of individually stabilized SPION. The colloidal stability extends to control over evasion of macrophage clearance and stimulated uptake by SPION functionalized with protein ligands, which is a key requirement for targeted MRI.
EVALuna2:214810